Efek samping terapi radiasi penderita kanker kepala dan leher pada kelenjar saliva - Barunawaty Yunus (DiscoverSys Inc., 2008)
Nasopharyngeal cancer has different malignancy types, based on its location. Themost frequent type of nasopharyngeal cancer is carcinoma of squamous cell whichhappens on cells inside nose, mouth, and throat. The rare types happened such assalivary gland tumor, lymphoma, and sarcoma. There are three main therapies totreat nasopharyngeal cancer; they are radiation therapy, surgery, and chemotherapy.The main treatment is radiation therapy or surgery and chemotherapy or combinationboth of them. Chemotherapy is often conducted as an additional treatment.Combination treatment between those three treatments optimally can be used fornasopharyngeal cancer patient based on the location and disease stadium. Radiationtherapy on nasopharyngeal cancer can caused some side effects, such as mucositis,salivary gland dysfunction, taste sense dysfunction and malnutrition, tooth disorders,bone transforming, cutaneous transforming, nerve disorders, decreasing ofintellectual, lost of hearing sense, complication of malignant cancer caused byradiation, and intracranial bleeding.